Comparing upper limb motor recovery in subacute ischaemic stroke and intracerebral haemorrhage: A Systematic Review. [version 2; peer review: 1 approved, 2 approved with reservations] - Sally Davenport; Lara Grima; Andy Vail; Adrian R. Parry-Jones; Ulrike Hammerbeck (Health Open Research)
Background The pathophysiology and medical management between ischaemic stroke and intracerebral haemorrhage differ as do their functional independence and mortality outcomes. This paper aims to establish whether their respective upper limb motor impairment and recovery differ. This information could inform discussions with patients about their recovery prognosis as well as identify appropriate rehabilitation settings. Methods A PROSPERO registered systematic search of three databases (MEDLINE, CINAHL, Embase) identified studies that measured upper limb motor function (Fugl-Meyer assessment scale for upper extremity) in participants with first stroke (ischaemic stroke or intracerebral haemorrhage) within 31 days post-stroke and at least one follow-up assessment. Risk of bias was assessed using the Critical Appraisal Skills Programme. Results The search identified 1108 studies of which three met inclusion criteria, with a total of 258 participants (200 ischaemic stroke, 58 intracerebral haemorrhage). All studies had low to moderate risk of bias. At baseline, participants with intracerebral haemorrhage had greater upper limb motor impairment on the Fugl-Meyer assessment scale, but at six months post-stroke, the stroke subtypes reached similar upper limb motor function. Improvements were greatest early after stroke. Conclusions Despite greater severity at baseline, intracerebral haemorrhage survivors appeared to reach the same level of arm function at six months post stroke. However, these findings need to be interpreted with caution due to limited studies and small number of participants included in this review and warrant further research. PROSPERO registration CRD42020159110 (19/02/2020).